Determinants of Domestic Investment in Nigeria - Izuchukwu Nnoje, PhD, Fr. Andrew; Ifeoma Emmanuella, PhD, Nwokoye; Gift Oke, Dickson; Christopher Osigbemeh, Ugbodaga (American Journal of Economics and Business Management, 2023)
This study examines the determinants of domestic investment in Nigeria, focusing on the effects of per capita income, consumption expenditure, savings, interest rate, and debt burden. Using time-series data from 1999 to 2023 obtained from the National Bureau of Statistics and Central Bank of Nigeria, the study employs the Ordinary Least Squares (OLS) regression technique to analyze the relationships between these variables and domestic investment. The results reveal that per capita income and savings have a positive and statistically significant impact on domestic investment, with coefficients of 0.36937 (p = 0.0033) and 0.19066 (p = 0.0000), respectively. In contrast, consumption expenditure (-0.48292; p = 0.0004), interest rate (-0.21753; p = 0.0001), and debt burden (-0.23448; p = 0.0048) exhibit negative and significant effects. The model’s R-squared value of 0.63945 indicates that approximately 64% of the variation in domestic investment is explained by the independent variables. The study concludes that while income growth and savings are critical for boosting investment, excessive consumption, high borrowing costs, and unsustainable debt burdens significantly constrain it. Recommendations include enhancing income levels through job creation and sectoral investment, promoting savings through financial inclusion, reducing borrowing costs by stabilizing interest rates, and managing debt burdens prudently. The study highlights the critical need for policies that foster a conducive environment for investment, which is pivotal for Nigeria’s economic growth, improved financial stability, and global competitiveness. These findings have profound implications for policymakers aiming to achieve sustainable development and economic resilience.